Intro stats. - De Veaux, Richard D., ....-; Bock, David E., ....-; Velleman, Paul F., 1949- (Boston : Pearson, 2009)
I. Exploring and Understanding Data 1. Stats Starts Here 2. Data 3. Displaying and Describing Categorical Data 4. Displaying and Summarizing Quantitative Data 5. Understanding and Comparing Distributions 6. The Standard Deviation as a Ruler and the Normal Model Review of Part I: Exploring and Understanding Data II. Exploring Relationships between Variables 7. Scatterplots, Association, and Correlation 8. Linear Regression 9. Regression Wisdom 10. Re-expressing Data: Get It Straight! Review of Part II: Exploring Relationships Between Variables III. Gathering Data 11. Understanding Randomness 12. Sample Surveys 13. Experiments and Observational Studies Review of Part III: Gathering Data IV. Randomness and Probability 14. From Randomness to Probability 15. Probability Rules! 16. Random Variables 17. Probability Models Review of Part IV: Randomness and Probability V. From the Data at Hand to the World At Large 18. Sampling Distribution Models 19. Confidence Intervals for Proportions 20. Testing Hypotheses about Proportions 21. More about Tests 22. Comparing Two Proportions Review of Part V: From the Data at Hand to the World at Large VI. Learning about the World 23. Inferences about Means 24. Comparing Means 25. Paired Samples and Blocks Review of Part VI: Learning About the World VII. Inference When Variables are Related 26. Comparing Counts 27. Inferences for Regression Review of Part VII: Inference When Variables Are Related 28. Analysis of Variance-on the CD 29. Multiple Regression-on the CD APPENDIXES A. Answers B. Photo Acknowledgements C. Index D. Tables and Selected Formulas
Keywords: Statistiek